Women’s Political Interest in Political Parties: a Gender Strategy - Adelina, Shelly; Soetjipto, Any (Yayasan Jurnal Perempuan, 2014)
Analysis of the gender strategy in the three largest political parties which dominate the legislative period 2009-2014, namely the Democratic Party, the Golkar Party and the Indonesian Democratic Party of Struggle (PDI-P) shows several findings that can be reflected to travel to face election. First, third parties accounted for the most number of women seats in the national parliament. Second, as the dominant parties through the fractions in the legislature, three showed no provisions regarding how the policies and strategies of political parties in efforts to achieve gender equality and gender mainstreaming strategies not found in political parties. Third, strategies that are present in the party institutions only tangible Department of Women as women focal point. Beyond that, the strategy of increasing the representation of women is based on justice, equality, and gender equity was absent.